The Modular Geometry of Precast Concrete for Highway Drainage Channel - stanto, Kelik I; Astuti, Eka Febri; Tumangger, Ranto; Zulkarnain, Iskandar; Agustina, Resti (Politeknik Negeri Bengkalis, 2024)
This research is based on the phenomenon of failure of masonry drainage channels, especially in locations withsteep to very steep slopes. Observing the flow behavior and mechanical properties of the masonry, it is possible due to theerosion of the bottom to the foot of the channel so that the masonry collapsed and/or due to side soil pressured which causedthe masonry failure. It could be overcome by replacing the masonry with precast concrete. The obstacle of precast concreteimplementation in low cost projects is involvement of heavy equipment when erecting precast concrete for drainage channel(e.g. U-Ditch) which is available on the market. This research aims to design the geometry and dimensions of precastcomponents for open channel of drainage with limitations: component weight (kg/component) is limited so that it could belifted by man power and is able to flow a design discharge ≥ 0.5 m3/s at 1.5 m /s. Channel was divided into 4 components,namely: foundation (F), bed (B, type I and II), wall (W), and channel cap (C) with 6 cm of thickness, 1:10 (H:V) of wallslope channel, and 75 cm of each component length. Each component weighs no more than 50 kg, so could be carried outwithout heavy equipment when constructed. The weights of each component are 39.8 kg, 45.36 kg, 28.8 kg, 37.8 kg, and21.45 kg for foundation, bed type I, bed type II, wall, and channel cap.